A comparison of Selected Photogrammetric Techniques for Creating 3D Models of Cultural Objects with Specular Surface - Christova, Andrea (Πανεπιστήμιο Πελοποννήσου, 2020)
As specular surfaces present a known challenge for most scanning and surface capturing technologies in terms of 3D model creation, the purpose of this study is to present, explore and compare three selected approaches for creating digital 3-dimensional representations of existing historical liturgical objects which have a specular (i.e. reflective, mirror-like) surface. Based on the interest of the HospitallerOrder of St. John of God in Bratislava, Slovakia to have their object inventory digitized for their internal documentation purposes, two studied objects - a silver-plated brass ciborium and a stainless-steel crucifix - were as a trial subjected to image capturing by a digital camera under three different conditions in an effort to minimize the effect of the reflected light. The first approach was using diffused light only, then cross-polarization was applied, while for the third approach a scanning spray was used. The acquired data was used for the creation of the respective 3D models of these objects. In the first two cases the data was used for both the model and the texture, whereas for the third option the data was used for creating the model only, while data from CPL (cross-polarization) was utilized for the texture due to the real surface being covered in white layer created by the spray. The selected techniques are discussed with their main features, while presenting the respective outcomes in the form of digital 3D object models, which are compared against each other in terms of output quality. The most accurate 3D models were produced by cross-polarization.
Keywords: Φωτογραμμετρία; Τρισδιάστατη απεικόνιση στην αρχαιολογία; Φηφιακή διατήρηση; Πολιτιστική κληρονομιά -- Προσομοίωση με υπολογιστή; Digitization; Photogrammetry; Structure from Motion; 3D models; Specular – shiny – glossy – reflective surfaces; Cultural heritage; Ψηφιοποίηση; Φωτογραμμετρία; Structure from Motion; 3D μοντέλα; Κατοπτρικές– λαμπερές – γυαλιστερές– αντανακλαστικές επιφάνειες; Πολιτιστική κληρονομιά